2008
DOI: 10.1182/blood-2007-09-113860
|View full text |Cite
|
Sign up to set email alerts
|

Absence of SKP2 expression attenuates BCR-ABL–induced myeloproliferative disease

Abstract: BCR-ABL is proposed to impair cell-cycle control by disabling p27, a tumor suppressor that inhibits cyclin-dependent ki-nases. We show that in cell lines p27 expression is inversely correlated with expression of SKP2, the F-box protein of SCF SKP2 (SKP1/Cul1/F-box), the E3 ubiq-uitin ligase that promotes proteasomal degradation of p27. Inhibition of BCR-ABL kinase causes G 1 arrest, down-regulation of SKP2, and accumulation of p27. Ectopic expression of wild-type SKP2, but not a mutant unable to recognize p27,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 45 publications
2
65
0
Order By: Relevance
“…17 Activation of signal transducer and activator of transcription 5 (STAT5) by JAK2V 617 F also leads to increased transcription of Skp2, a subunit of ubiquitin E3 ligase, which further promotes p27/Kip1 degradation. 18,19 Moreover, the normal control on overexuberant cell growth, mediated by the suppressor of cytokine signaling 3 (SOCS3), which acts to regulate JAK2 activity, is also abrogated by JAK2V 617 F in BaF/3 cells. disease pathogenesis have yet not been performed for many of these mutant kinases.…”
Section: Introductionmentioning
confidence: 99%
“…17 Activation of signal transducer and activator of transcription 5 (STAT5) by JAK2V 617 F also leads to increased transcription of Skp2, a subunit of ubiquitin E3 ligase, which further promotes p27/Kip1 degradation. 18,19 Moreover, the normal control on overexuberant cell growth, mediated by the suppressor of cytokine signaling 3 (SOCS3), which acts to regulate JAK2 activity, is also abrogated by JAK2V 617 F in BaF/3 cells. disease pathogenesis have yet not been performed for many of these mutant kinases.…”
Section: Introductionmentioning
confidence: 99%
“…65 In addition to p27, Skp2 expression can also be regulated by JAKV617F, where the protein is transcriptionally induced by activated STAT5. 87,88 Interestingly, shRNA-mediated knockdown of JAK2V617F leads to loss of p27-Y88 phosphorylation and stabilization of p27 without changes in Skp2 levels, indicating that p27 regulation by JAK2V617F can occur independently from Skp2 regulation.…”
Section: Jak2 Binds and Directly Phosphorylates P27mentioning
confidence: 99%
“…Skp2 has been characterized to exhibit its oncogenic function via targeting of its substrates including p27 (7,8), p21 (9), p57 (10) and Forkhead box protein O1 (FOXO1) (11,12). Engineered mouse models revealed that conditional depletion of Skp2 in mice suppressed tumor growth in T cell lineage (13), B cell lineage (14), bone marrow (15), liver (16,17), breast (18), prostate (19) and skin cancer (20). Consistently, upregulation of Skp2 in mice enhanced tumor growth in lymphoma (21), prostate cancer (19) and breast tumor (18).…”
Section: Introductionmentioning
confidence: 99%